ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL EKSPONEN BERDASARKAN PROSEDUR NEWMAN - Khoirunnisa, Fita; Utami, Rini (LPPM Universitas Bina Bangsa, 2024)
This research aims to determine the types of errors made by students when working on exponent problems. Apart from that, research also analyzes the factors that cause mistakes made by students. Errors in working on questions consist of reading errors, understanding errors, transformation errors, processing errors and errors in writing the final answer. This research uses descriptive qualitative data analysis. Research subjects were determined using purposive sampling techniques. The research results showed that students made errors in understanding, transformation errors, process errors and errors in writing the final answer. The factors that cause this are students being in a hurry to work on questions, students also being unable to continue the process of working on questions because students do not understand the material and students are not careful in working on questions